UMTS vs LTE Coverage by signal level and overlapping zone A Comparative Study - Yousif Masood, Marola Yousri; Abdallah, Dr. Ahmed Salah; Nabi Mustafa, Dr. Amin Babiker A/ (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The purpose of this research is to compare between UMTS and LTE especially in coverage by signal level and overlapping zones . Mobile communication technologies are aiming at responding to the growing demand for higher connectivity . In telecommunication LTE (4G) is the fourth generation of mobile communication technology standards, it is a successor of UMTS (3G), third generation standards. Standards specify how airwaves must be used for transmitting information (voice and data). All radio access technologies have to solve the same problems: to divide the finite RF spectrum among multiple users as efficiently as possible. UMTS use CDMA. LTE use OFDM. Code-division multiple access (CDMA) This uses a digital modulation called spread spectrum which spreads the voice data over a very wide channel in pseudorandom fashion using a user or cell specific pseudorandom code. The receiver undoes the randomization to collect the bits together and produce the original data. As the codes are pseudorandom and selected in such a way as to cause minimal interferenceto one another, multiple users can talk at the same time and multiple cells can share the same frequency. This causes an added signal noise forcing all users to use more power, which in exchange decreases cell range and battery life. Orthogonal Frequency Division Multiple Access (OFDMA) uses bundling of multiple small frequency bands that are orthogonal to one another to provide for separation of users. The users are multiplexed in the frequency domain by allocating specific sub-bands to individual users. This is often enhanced by also performing TDMA and changing the allocation periodically so that different users get different sub-bands at different times. An extensive examination of the UMTS and LTE architecture will be explained.